Application of Contextual Teaching and Learning (CTL) Methods in Improving the Ability to Write Description of Students of Class VII SMP Negeri 14 Tanralili Maros Regency - Jumriati Jumriati (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to improve the ability to write descriptive essays through the Contextual Teaching and Learning (CTL) method in class VII SMP Negeri 14 Tanralili Maros.The type of research used is classroom action research which is carried out in two cycles, namely cycle I and cycle II consisting of planning, implementation, observation, and reflection stages. The subjects of this study were class VII students, a total of 35 students. The object of research is the ability to write descriptive essays through the Contextual Teaching and Learning (CTL) method. Data collection techniques in this study are tests, observations, and interviews. The analysis technique in this study uses quantitative and qualitative analysis. The results showed that learning to write descriptive essays using the Contextual Teaching and Learning (CTL) method could improve the writing skills of grade VII students. The increase in students' attitudes and activities during the learning process of writing descriptive essays increased. The average value of the ability to write descriptive essays in the first cycle was 49.40% while the increase in the average value of the ability to write descriptive essays in the second cycle increased by 81.51%. Thus, it can be concluded that the application of the Teaching and Learning (CTL) method in improving the ability to write descriptive essays for class VII students of SMP 14 Tanralili Maros has been categorized as very good.